2007
DOI: 10.1103/physrevlett.99.137204
|View full text |Cite
|
Sign up to set email alerts
|

Polarized-Neutron Study of Spin Dynamics in the Kondo InsulatorYbB12

Abstract: Inelastic neutron scattering experiments have been performed on the archetype compound YbB(12), using neutron polarization analysis to separate the magnetic signal from the phonon background. With decreasing temperature, components characteristic for a single-site spin-fluctuation dynamics are suppressed, giving place to specific, strongly Q-dependent, low-energy excitations near the spin-gap edge. This crossover is discussed in terms of a simple crystal-field description of the incoherent high-temperature sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 17 publications
7
43
0
Order By: Relevance
“…YbB 12 is a typical Kondo insulator [2,3] with a fluctuating Yb valence around 2.9+ [4,5]. According to infrared spectroscopy studies [6], the Drude response is sharply decreased below ∼80 K and an indirect gap of ∼15 meV opens at 8 K. Inelastic neutron scattering studies reported the spin gap of 15 meV in the insulating state [7,8]. This crossover is frequently explained by a narrow-gap formation due to hybridization between the conduction band electrons and the localized f electrons (c-f hybridization) within the scheme of the periodic Anderson model.…”
mentioning
confidence: 99%
“…YbB 12 is a typical Kondo insulator [2,3] with a fluctuating Yb valence around 2.9+ [4,5]. According to infrared spectroscopy studies [6], the Drude response is sharply decreased below ∼80 K and an indirect gap of ∼15 meV opens at 8 K. Inelastic neutron scattering studies reported the spin gap of 15 meV in the insulating state [7,8]. This crossover is frequently explained by a narrow-gap formation due to hybridization between the conduction band electrons and the localized f electrons (c-f hybridization) within the scheme of the periodic Anderson model.…”
mentioning
confidence: 99%
“…The INS study of YbB 12 reveals two spin gap type excitations near 15.5 meV and 20 meV [70]. From the Q and temperature dependence it was found that the origin of 15.5 meV peak in YbB 12 is very similar to 14 meV peak in SmB 6 .…”
Section: (B) Hybridization Gap Study In the Kondo Insulator Cefe 2 Al 10mentioning
confidence: 67%
“…From the Q and temperature dependence it was found that the origin of 15.5 meV peak in YbB 12 is very similar to 14 meV peak in SmB 6 . The 20 meV peak in YbB 12 was identified as manifesting a transition from a localized Kondo singlet with a gap to a magnetic state [70]. Further two spin gaps at 27 meV and 50 meV have been also observed through INS study on TKI CeOs 4 Sb 12 , which been interpreted as indirect (or spin gap) and direct (or charge gap) [75].…”
Section: (B) Hybridization Gap Study In the Kondo Insulator Cefe 2 Al 10mentioning
confidence: 88%
See 1 more Smart Citation
“…The spin resonance is a common phenomenon in the gap of, e.g. heavy fermion (HF) unconventional superconductors [23][24][25][26][27][28] , but it may also exist in the hybridization or hidden order gap of non-superconducting Kondo compounds [29][30][31][32][33] (for a review see Ref. 34).…”
Section: Introductionmentioning
confidence: 99%